New schedule and a call for guest authors - Editorial Board (In the Library with the Lead Pipe, 2009)
Since our launch last October, In the Library with the Lead Pipe has been publishing a new post nearly every Wednesday. As writers, drafting long-form, in-depth posts on a weekly basis has proved challenging, even with the contributions of our talented guests. We’ve heard from many of you that, as readers, you’ve found it hard [...]